The Impact of Digital Transformation on Office Management Efficiency - Habes Al-Saudi , Nehad; Hammood Flayyih, Hakeem (Journal of Economics and Administrative Sciences, 2024)
Purpose: The study examines digitalization literature on office administration efficiency in firms from management, marketing, finance, and accounting in Jordan Companies.Theoretical framework: The questionnaire regularly compliments Digital Transformation (DT) on Office Management Efficiency (OME) contributions. Participants say digitalization improves job effectiveness, validating the findings. The concepts were supported by multiple questions.Design/methodology/approach: We focused our analysis on 34 research papers related to DT and OME for the period from 2017 to 2024. Based on bibliometric analysis, this paper highlights the prevailing trend of current study in the field of DT and OME, by providing a detailed bibliometric analysis of the research trend and development for the last eight years, due to the increasing reliance on DT, including investigating the countries, journals and keywords of the research.Findings: Statistical data and participant answers reveal that DT improves OME across disciplines. Results show digitization's advantages and how digital tools, and technology have enhanced production.Research, Practical & Social implications: DT may boost organizational efficiency. A key benefit of DT for office administration is automation. Automation may save workers time and allow them to focus on important duties. Technology like robotic process automation may reduce human labor and boost production. Digital technology can streamline processes, automate tasks, increase communication, and boost performance using data analytics. Businesses must prioritize DT to compete and grow sustainably in the digital age.Originality/value: Manage documents, communicate, schedule, and delegate tasks. Digital platforms help office managers streamline, collaborate, and accomplish tasks on time. Finaly, this study provides evidence of the lack of interest in the impact of DT on office management. Finally, the data analysis identifies several potential research issues to be investigated in relation to this relationship, which serve as an area for future research.